Development of Novel Glyphosate-Tolerant Japonica Rice Lines: A Step Toward Commercial Release - Cui, Ying; Huang, Shuqing; Liu, Ziduo; Yi, Shuyuan; Zhou, Fei; Chen, Hao; Lin, Yongjun (Frontiers in Plant Science, 2016)
Glyphosate is the most widely used herbicide for its low cost and high efficiency. However, it is rarely applied directly in rice field due to its toxicity to rice. Therefore, glyphosate-tolerant rice can greatly decrease the cost of rice production and provide a more effective weed management strategy. Although several approaches to develop transgenic rice with glyphosate tolerance have been reported, the agronomic performances of these plants have not been well evaluated, and the feasibility of commercial production has not been confirmed yet. Here, a novel glyphosate-tolerant gene cloned from the bacterium Isoptericola variabilis was identified, codon optimized (designated as I. variabilis-EPSPS*), and transferred into Zhonghua11, a widely used japonica rice cultivar. After systematic analysis of the transgene integration via PCR, Southern blot and flanking sequence isolation, three transgenic lines with only one intact I. variabilis-EPSPS* expression cassette integrated into intergenic regions were identified. Seed test results showed that the glyphosate tolerance of the transgenic rice was about 240 times that of wild type on plant medium. The glyphosate tolerance of transgenic rice lines was further evaluated based on comprehensive agronomic performances in the field with T3 and T5 generations in a two-year assay, which showed that they were rarely affected by glyphosate even when the dosage was 8400 g ha-1. To our knowledge, this is the first demonstration of the development of glyphosate-tolerant rice lines based on a comprehensive analysis of agronomic performances in the field. Taken together, the results suggest that the selected glyphosate-tolerant rice lines are highly tolerant to glyphosate and have the possibility of commercial release. I. variabilis-EPSPS* also can be a promising candidate gene in other species for developing glyphosate-tolerant crops.